Esterification of p-hydroxybenzoic acid with glucose using a Î³-Al2O3/SO4 catalyst - Elfia Siska yasa Putri; Widajanti Wibowo; Soleh Kosela (Universitas Ahmad Dahlan, 2019)
Esterification of p-hydroxybenzoic acid with glucose can be expected to produce esters. The rate of esterification reaction is usually very slow and, therefore, needs an acid catalyst to accelerate it. This research examined the performance of a heterogeneous catalyst made of Î³-Al2O3 impregnated with a protic acid, H2SO4. The heterogeneous catalyst, Î³-Al2O3/SO4, was characterized using XRD, XRF, and BET methods. The esterification reactions were conducted using dimethyl sulfoxide (DMSO) solvent at a temperature of 1000C and observed after they lasted for 1 to 24 hours (reaction time). The esterification of p-hydroxybenzoic acid with glucose used two catalysts, namely 3% SO42-/Al2O3 and 5% SO42-/Al2O3. The reaction products were analyzed using HPLC, IR, and LC-MS methods. The % yield was the highest at Hour 24 for both catalysts, while the % conversion fluctuated during the esterification time. The LC-MS showed that the three produced esters had molecular weights of 300, 420, and 540.